CHEMISORPTION AND EPITAXIAL-GROWTH - STRUCTURAL AND KINETIC-STUDIES OF HALOGEN INTERACTIONS WITH VANADIUM AND CHROMIUM SURFACES - Reed, A; Lambert, R; Foord, J (1983)
A unified surface chemistry has emerged from studies of halogen adsorption and halide corrosion on the (100) faces of Cr and V. Dissociated halogen overlayers form with high sticking probability at low coverages and pronounced precursor state effects are exhibited. As θ increases above 0.5, attractive interactions originally present within the adlayer become repulsive and uniaxial compression of the adsorbed phase occurs. Thermal desorption is complex since thermal conversion yields a range of products; by consideration of the relevant thermodynamic and kinetic parameters governing the desorption process, a general model accounting for these observations has been formulated. Corrosion of the metal substrate occurs at high gas exposures resulting in the formation of dihalides by an island growth mechanism. These halide films adopt a common layer structure and orientation. Their stoichiometry and growth rate depend sensitively on the speed of interdiffusion through the film and the residence lifetime of the weakly bound X2 precursor via which corrosion proceeds. Modifications to the V(100)/Cl2 chemistry upon coadsorbing potassium were investigated. KCl forms in preference to VCl2, although microcrystallites of both halides result at high exposures. Diffusion of Cl between the two corrosion phases is facile at 300 K, and esd takes place only from the KCl phase. © 1983.